Supporting Patent Mining by using Ontology-based Semantic Annotations - Ghoula, Nizar; Khelif, Khaled; Dieng-Kuntz, Rose (Proceedings of the IEEE/WIC/ACM International Conference on Web Intelligence, 2007)
Semantic web approach seems interesting for supporting content mining of millions of patents accessible through the Web. In this paper, we describe our approach for generating semantic annotations on patents, by relying on the structure and on a semantic representation of patent documents. We use both the structure of the patent documents and their textual contents processed by Natural Language Processing (NLP) tools. This method, primarily aimed at helping biologists use patent information can be generalized to all kinds of domains or of structured documents.